Antecedents of corporate entrepreneurship - R. Van Wyk (South African Journal of Business Management, 2012)
Businesses should strive to identify and nurture internal organisational factors that cultivate a dynamic entrepreneurial culture. This paper scrutinizes the contribution of the internal organisational factors, measured by market orientation, flexibility and job satisfaction, to intrapreneurship, as measured by the Corporate Entrepreneurship Assessment Instrument (CEAI). Information from a sample of 333 managers explores the relationships of corporate entrepreneurship with different work variables by means of Product-Moment Correlation, Multiple Regression Analyses and Structural Equation Modelling. Structural Equation Modelling confirms that four of the corporate entrepreneurship factors were predicted reasonably well by means of the market orientation, flexibility and job satisfaction sub-scales. The article attempts to fill the research gap of identifying which market orientation, flexibility and job satisfaction factors play an important role in facilitating corporate entrepreneurial actions.